2017
DOI: 10.1537/ase.160916
|View full text |Cite
|
Sign up to set email alerts
|

Paleopathology in the Piraino mummies as illustrated by X-rays

Abstract: This paper presents the first radiological investigation of a collection of Sicilian mummies held in a crypt beneath the Mother Church of Piraino, Italy. The chamber contains 26 preserved bodies of religious dignitaries, either conserved vertically in special wall niches or horizontally on wooden shelves. The majority of bodies are clothed, and transportation outside of the crypt was not feasible. Therefore assessment of the remains via paleoradiological methods appeared to be the most convenient approach to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Its actual cause is unknown; however, DISH is more prevalent in obese, diabetic and/or gouty individuals (Mays, 2009; Kiss, Szilagyi, Paksy, & Poor, 2002; Giuffra, Minozzi, Vitiello, & Fornaciari, 2017). The disease is commonly associated with ancient individuals of high status or clergymen, which followed a “monastic way of life” (Bondioli, Nava, Rossi, & Sperduti, 2016; Jankauskas, 2003; Kacki et al, 2018; Müldner & Richards, 2007; Piombino‐Mascali, Zink, & Panzer, 2017; Rogers & Waldron, 2001; Verlaan, Oner, & Maat, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Its actual cause is unknown; however, DISH is more prevalent in obese, diabetic and/or gouty individuals (Mays, 2009; Kiss, Szilagyi, Paksy, & Poor, 2002; Giuffra, Minozzi, Vitiello, & Fornaciari, 2017). The disease is commonly associated with ancient individuals of high status or clergymen, which followed a “monastic way of life” (Bondioli, Nava, Rossi, & Sperduti, 2016; Jankauskas, 2003; Kacki et al, 2018; Müldner & Richards, 2007; Piombino‐Mascali, Zink, & Panzer, 2017; Rogers & Waldron, 2001; Verlaan, Oner, & Maat, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although the rational of Kaplan et al, (1994) can also be applied to cranial osteomata, Eshed et al (2002) suggested that, based on their histological features, these lesions be reclassified as hamartoma, a malformation that resembles a neoplasm but results from faulty development. In palaeopathological case reports of osteomata, these lesions are referred to as tumours, and the debate regarding their status as a neoplasm is either not mentioned or not discussed (Blau, 2006; Castro et al, 2019; Dąbrowski et al, 2015; Galassi et al, 2020; Giuffra et al, 2019; Licata, Borgo, Armocida, Nicosia, & Ferioli, 2016; Piombino‐Mascali, Zink, & Panzer, 2017; Premužić & Šikanjic, 2013; Odes et al, 2018; Smith, 2010; Zias, 2006). Bartelink and Wright (2011) seem to be the only researchers who did note this debate in their report of a mandibular tumour from Guatemala, dated to the 6 th to 9 th century CE.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its small case size for statistical evaluation, the example used showed significant differences between mummification types. These differences indicate that the embalming methods used for the anthropogenically mummified Sicilian mummies [ 14 , 31 , 32 ] produced an especially high preservation status of soft tissues of the head and spine including external as well as internal structures of the head, and soft tissue structures of the musculoskeletal system as well as peripheral nerves of the spine. Therefore, the preservation status seemed to depend more upon the topography rather than upon the kind of soft tissue in these cases.…”
Section: Discussionmentioning
confidence: 99%